Animal Biotelemetry - Klimley, A. Peter
Animal Biotelemetry is an open access peer-reviewed journal that publishes the results of studies utilizing telemetric techniques (including biologgers) to understand physiological, behavioural, and ecological mechanisms in a broad range of environments (e.g. terrestrial, freshwater and marine) and taxa. The journal also welcomes descriptions and validations of newly developed tagging techniques and tracking technologies, as well as methods for analyzing telemetric data.